2016
DOI: 10.21037/atm.2016.ab064
|View full text |Cite
|
Sign up to set email alerts
|

AB064. Estimation of direct and indirect costs and quality of life of patients with chronic obstructive pulmonary disease and their burden on Greek Health System

Abstract: Background: Lung cancer remains the leading cause of cancer-related deaths worldwide and novel therapeutic approaches targeting crucial pathways are urgently needed to improve its treatment. Differentiation-based therapeutics (Methylxanthines) and phosphodiesterase inhibitors (type 4 and 5), have been implicated in cancer treatment. Our objectives were to capture any potential anti-tumor effect of these drug combinations with chemotherapeutic agents in vitro. Methods: Theophylline as Methylxanthines, Roflumila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 0 publications
1
7
1
Order By: Relevance
“…From a review of the literature to date, only a limited number of published studies have focused on the costs of terminal-phase lung cancer care. In the Greek context, a recently published prospective study 20 estimated the costs of patients with lung cancer for a period of 32 months from diagnosis to the end of registry and found that the cost of chemotherapy was the main cost driver, a finding consistent with the findings of our study, while the indirect cost was higher for patients than their caregivers. However, the clinical procedures used during treatment of patients with end-stage lung cancer were not recorded and their direct medical costs not estimated.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…From a review of the literature to date, only a limited number of published studies have focused on the costs of terminal-phase lung cancer care. In the Greek context, a recently published prospective study 20 estimated the costs of patients with lung cancer for a period of 32 months from diagnosis to the end of registry and found that the cost of chemotherapy was the main cost driver, a finding consistent with the findings of our study, while the indirect cost was higher for patients than their caregivers. However, the clinical procedures used during treatment of patients with end-stage lung cancer were not recorded and their direct medical costs not estimated.…”
Section: Discussionsupporting
confidence: 89%
“…Recently, a prospective analysis estimated the direct and indirect costs of lung cancer incurred in a Greek University Pulmonary Department with chemotherapy drugs constituting the highest factor of total direct cost. 20 In the latter study, the health-care costs for patients with end-stage lung cancer during the last months of life were not estimated. In 2011, a nationwide study calculated hospital costs for the treatment of smoking-attributable diseases in Greece and demonstrated that lung cancer–related costs for that year were approximately €38.2 million.…”
Section: Introductionmentioning
confidence: 98%
“…We found that a participant’s lost days of productivity were longer than those of the family caregiver during the phase of diagnosis. The results were different from a previous study 26. This finding could be partially explained by the low employment rate of family caregivers.…”
Section: Discussioncontrasting
confidence: 99%
“…Although prior research had estimated non-medical costs for breast cancer screening, cervical cancer screening and colon cancer screening,8–11 most studies evaluated the time costs related to lost work days and transportation costs among lung cancer survivors after cancer diagnosis 12 25–27. Cressman et al estimated the time and transportation costs associated with lung cancer screening in the PanCan study 14.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation